Environmental Sustainability Goal and the Effect of Resources Extrication: A "Give and Take Perspective” - Uju Violet Alola; Andrew Adewale Alola; Serdar Cop; Marymagdaline Enowmbi Tarkang (International Journal of Renewable Energy Development, 2022)
Environmental sustainability is one of the vast research areas in the globe. Most industries are not left out in the quest for a sustainable environment including the hotel industry. Also, customers look for environmental friendly hotel to patronize. With this vast knowledge, the current study takes into account the relationship between green training and green employee involvement, with the mediating effect of perceived behavioural control. The sample of 306 was collected from 4 and 5-star hotel in Turkey in 2020. The study assessed the data with AMOS 20 to hypothesize the relationship between the variables. Findings confirmed that there is a positive impact of green training on perceived behavioural control, organizational citizenship behaviour towards the environment and green employee involvement. In addition, results also validated the positive effect of perceived behavioural control on organizational citizenship behaviour and green employee involvement. It contributes significantly to the ongoing research in the field of green training in the hotel industry in Turkey. These outcomes are supportive to Turkey’s hotel industry green management and employee behavioural actions to the environment.